Type 1 versus Type 2 calreticulin mutations in essential thrombocythemia: A collaborative study of 1027 patients. Issue 8 (16th May 2014) - Tefferi, Ayalew; Wassie, Emnet A.; Guglielmelli, Paola; Gangat, Naseema; Belachew, Alem A.; Lasho, Terra L.; Finke, Christy; Ketterling, Rhett P.; Hanson, Curtis A.; Pardanani, Animesh; Wolanskyj, Alexandra P.; Maffioli, Margherita; et al.
<x xml:space="preserve">Abstract</x> CALR (calreticulin) trails JAK2 as the second most mutated gene in essential thrombocythemia (ET). Mutant CALR in ET is a result of frameshift mutations, caused by exon 9 deletions or insertions; type‐1, 52‐bp deletion (p.L367fs*46), and type‐2, 5‐bp TTGTC insertion (p.K385fs*47) variants constitute more than 80% of these mutations. The current study includes a total of 1027 patients divided into test (n = 402) and validation (n = 625) cohorts. Among the 402 ET patients in the test cohort, 227 (57%) harbored JAK2, 11 (3%) Myeloproliferative leukemia virus oncogene (MPL), and 114 (28%) CALR mutations; 12% were wild‐type for all three mutations (i.e., triple‐negative). Among the 114 patients with CALR mutations, 51 (45%) displayed type‐1 and 44 (39%) type‐2 variants; compared to mutant JAK2, both variants were associated with higher platelet and lower hemoglobin and leukocyte counts. However, male sex was associated with only type‐1 (P = 0.005) and younger age with type‐2 (P = 0.001) variants. Notably, platelet count was significantly higher in type‐2 vs. type‐1 CALR‐mutated patients (P = 0.03) and the particular observation was validated in the validation cohort that included 111 CALR‐mutated ET patients (P = 0.002). These findings, coupled with the recent demonstration of preferential expression of mutant and wild‐type CALR in megakaryocytes, suggest differential effects of CALR variants on thrombopoiesis. Am. J. Hematol. 89:E121–E124, 2014. © 2014 Wiley Periodicals, Inc.